PEMANFAATAN MEDIA SOSIAL INSTAGRAM AKUN @MR.CREAMPUFF SEBAGAI PROMOSI DALAM MENINGKATKAN PENJUALAN - Ramadhan, Fadli Harisa; Firdaus, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Mr.creampuff is a sus cake food manufacturer established on January 22, 2014. Mr.creampuff introduces and uses Instagram as a promotional medium to attract the attention of its customers. Owner Mr.creampuff himself introduced his product through instagram at the beginning of 2014, through the promotion with instagram the business owner Mr.creampuff many profits from the results of the seller. Then there is a big enough opportunity to start selling the product that is done both offline and online through media instagram. In 2015 the demand from enthusiasts Mr.creampuff quite a lot, this cake producers have a lot of consumers and every day they receive orders from customers by using delivery or take away. In the end there stood a shop on the eagle street in early 2016.The purpose of this study is To determine the utilization of media instagram as a medium of communication in the promotion of sales, media utilization instagram as a marketing medium in sales promotion and know the use of social media instagram as a media binis in sales. This research uses qualitative research method with descriptive analysis. This research uses four person informant, owner Mr.creampuff, 2 employees of Mr.creampuff and 1 user who menfollow account Mr.creampuff selected by purposive sampling. Data collection techniques used are observation, interview, and documentation. Data validity technique used in this research is triangulation and extension of participation.The results obtained show that social media instagram can to facilitate communicate with the public or customers, From these features can make users of social media like to use the application and simplify for marketing and Able to give impact to attract many new visitors who are interested and may be will be a regular visitor in instagram account of the online business.proses promotion is getting a lot of profits and sales did not need to spend at allKeyword: Utilization Instagram,Promotion in Improving Sales